A CW electron accelerator. The planned design and electrophysical characteristics - Zavialov, N.V.; Zhelezov, S.A.; Nazarenko, S.T.; Porkhaev, V.V.; Punin, V.T.; Putevskoy, S.A.; Smetanin, M.L.; Telnov, A.V. (Вопросы атомной науки и техники, 2006)
This paper presents a project on a CW high-power electron accelerator. The main part of the accelerator consists of half-wave coaxial cavity resonator. The increment of electron energy is reached by repeated passing of an electron beam via full diameter of the cavity in median plain dividing its bulk into halves. Successive redirection of the electron beam into the cavity is performed by means of two rotary magnets. These magnets are placed outside the cavity. Main parameters of the accelerator are as follows: electron beam energy 1.5…7.5 MeV, average beam power above 300 kW, operating frequency 100 MHz.